Pengaruh Word Of Mouth dan Customer Engagement terhadap Kepercayaan Konsumen pada Produk Makanan dan Minuman dengan Kepuasan Pelanggan sebagai Variabel Intervening: Studi pada Konsumen Calf Kopi di Kota Semarang - Mahatma Maulana; I Made Sukresna (Faculty of Economics and Business Diponegoro University, 2026)
This study examines the influence of Word of Mouth (WOM) and Customer Engagement on Consumer Trust in Calf Kopi’s food and beverage products in Semarang, with Customer Satisfaction as an intervening variable.Employing a quantitative approach using Structural Equation Modeling (SEM), the research reveals that WOM and Customer Engagement significantly affect Customer Satisfaction (coefficients of 0.341 and 0.254, respectively), which mediates their relationship with Consumer Trust (indirect effects of 0.155 and 0.108).These findings underscore the pivotal role of WOM and Customer Engagement in fostering consumer trust within the local coffee industry. Managerial implications include strategies to enhance WOM through referral programs and boost engagement via interactive digital campaigns. The study contributes to relationship marketing theory and suggests future research to incorporate additional variables, such as service quality